Nota Kesepahaman Helsinki untuk Mengakhiri Konflik Aceh: Telaah Sosiologi Politik dan Histori - Suadi Zainal (Budapest International Research and Critics University, 2015)
The protected conflict between Free Aceh Movement (GAM) and Government of Indonesia (GoI) lasted nearly 30 years (1976-2005). It was solved with Memorandum of Understanding (MoU) signed on 15 August 2005 in Helsinki Finland which mediated by Crisis Management Initiative (CMI). Conse- quently GoI should establish a new law on the governing Aceh (LoGA) as a follow up of the MoU. But some articles of LoGA are contra on MoU and many issues remain unsolved. Nevertheless, this reality created oppor- tunities for economic and socio-politic development in Aceh. One great change is GAM transformed to political party and being the ruler in Aceh since 2006. Hence peace accord (MoU) has been lasting for 9 years, although Aceh is fragile right now. This paper explains the conflict settlement and constitution reform, and the impact on authority arrangement and relationship between Aceh-Indonesia after MoU Helsinki.